ANALYSIS OF THE IMPLEMENTATION OF STATISTICAL QUALITY CONTROL IN QUALITY CONTROL OF ARABICA COFFEE PRODUCTION PROCESS (A Case Study at PT. XYZ, Madiun Regency) - Pambudi Nurwantara, Ma'ruf; Ridwan, Ridwan; Arif Rosadi, Farchan (JALOW | Journal of Agribusiness and Local Wisdom, 2024)
The purposes of this study are to identify the quality control of Arabica’s production process, to determine the factors causing mismatches in the production process, and to formulate the strategies in improving Arabica A/WP 1 L’s product quality at PT. XYZ. The quality control uses Statistical Quality Control method with a variety of attributes. The study revealed that the quality control was in controlled conditions since the p-chart shown that the number of actual data samples were in the statistical control range with the value of 0.3206 for UCL and 0.1714 for LCL. Type of mismatch that had significant influence occurred in grain patterned coffee with a value of 869. Besides, the highest percentage of mismatches were patterned grain by 29.4%, perforated grain by 27.3%, and the outer skin with the small size by 26.6%, with the cumulative percentage was 83.3%. The factors affecting the mismatches were human, machine, method, raw material, and the environment. Thus, the proposed improvement strategies for the company are technical training, intensive sanitation scheduling, the Standard Operation Procedures formulation especially for the separation station (vis pulper and huller). Tempering HS dried coffee implementation, selective sorting of the coffee float on siphon tub, and adding 4 pieces LED lamp with power 40 watt as well as fan as the air conditioner.